2004
DOI: 10.3171/ped.2004.101.2.0059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective dorsal rhizotomy on need for orthopedic surgery for spastic quadriplegic cerebral palsy: long-term outcome analysis in relation to age

Abstract: The results of this study highlight the effect of SDR on gait status in children with spastic quadriplegic cerebral palsy. The percentage of patients needing orthopedic operations was not as high as reported previously. Parents indicated that SDR was beneficial to their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…10 Both the measure GMFM, and the classification GMFCS, have been found to be valid and reliable tools that are widely used in clinical work and research involving children with CP. The GMFM is frequently used to evaluate the effects of various interventions in children with CP, such as intensive physiotherapy, [11][12][13][14] botulinum toxin treatment, 15 selective dorsal rhizotomy, 16 and orthopaedic surgery. [17][18][19] The GMFM is a test specially designed and validated for measuring gross motor function and the change over time in children with CP.…”
mentioning
confidence: 99%
“…10 Both the measure GMFM, and the classification GMFCS, have been found to be valid and reliable tools that are widely used in clinical work and research involving children with CP. The GMFM is frequently used to evaluate the effects of various interventions in children with CP, such as intensive physiotherapy, [11][12][13][14] botulinum toxin treatment, 15 selective dorsal rhizotomy, 16 and orthopaedic surgery. [17][18][19] The GMFM is a test specially designed and validated for measuring gross motor function and the change over time in children with CP.…”
mentioning
confidence: 99%
“…A significant decrease in spasticity and range of motion was found was found 5 years after SDR in four studies 10,18,19,21 and in one study 20 years after SDR 14 . One Level IV study reported a significant improvement of gait performance in a subgroup of children that have been younger than 5 years old when SDR was performed 23 . There was no association between the age at the operation and outcome in any of the other studies.…”
Section: Discussionmentioning
confidence: 86%
“…However, the results in the body function and structure domain were not mentioned separately for the patients in the control group. Six further Level IV studies including 244 patients reported outcomes in the domain of body structure and body function 10,14,18,21,23,25 . A significant decrease in spasticity and range of motion was found was found 5 years after SDR in four studies 10,18,19,21 and in one study 20 years after SDR 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this review we focused on three previous reports from our department in which the relationships between orthopedic surgery and SDR were explored. 3,12,13 Our review is subdivided into four parts to address these three reports and also the need for spinal stabilization after SDR.…”
Section: Orthopedic Surgery Post-sdr: Objectives Of the Reviewmentioning
confidence: 99%